2014
DOI: 10.11648/j.ajbls.20140204.12
|View full text |Cite
|
Sign up to set email alerts
|

Sedative-Hypnotic Like Effect of the Essential Oil from the Leaves of Myrtus Communis on Mice

Abstract: Myrtus communis has been recommended for relief of insomnia in Ethiopian traditional medicine and aromatherapy. However, no pharmacological studies have yet evaluated its sedative-hypnotic like effect. The aim of this study was to determine if the essential oil of Myrtus communis has sedative-hypnotic like activity. The essential oil of Myrtus communis (500,600, 800, and 1000 mg/kg) were administered orally to Swiss albino mice of both sex, 60 minutes before pentobarbital injection (50 mg/kg). Latency to sleep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Data from the literature reported similar effects of newly synthesized analogues of myrtenal on the GABA-ergic system (100). Similar results for improved hypnotic effects of barbiturates in mice have been reported for Myrtus communis essential oil and water-alcohol plant extract (101,102). Our data of myrtenal's potentiating activity on classic hypnotic drugs (barbiturates) effects in combination (103) also confirm the results obtained by other researchers (77).…”
Section: Biological Effects Of Bicyclic Monoterpenoid Myrtenal (Alone)supporting
confidence: 90%
“…Data from the literature reported similar effects of newly synthesized analogues of myrtenal on the GABA-ergic system (100). Similar results for improved hypnotic effects of barbiturates in mice have been reported for Myrtus communis essential oil and water-alcohol plant extract (101,102). Our data of myrtenal's potentiating activity on classic hypnotic drugs (barbiturates) effects in combination (103) also confirm the results obtained by other researchers (77).…”
Section: Biological Effects Of Bicyclic Monoterpenoid Myrtenal (Alone)supporting
confidence: 90%
“…In Ethiopia, it is commonly called “addus” in Amharic. 3 – 7 It is grown in gardens of Addis Ababa. The plant is much more widespread than the herbarium collections indicate.…”
Section: Introductionmentioning
confidence: 99%
“…In one of our previous studies, the EO from the leaves of this plant was shown to have a muscle relaxing effect and also potentiate the hypnotic effect of pentobarbital. 7 …”
Section: Introductionmentioning
confidence: 99%
“…The essential oil of common myrtle revealed sedative-hypnotics. 68 Two years later, another controversial finding revealed that there was no induction of hypnosis. However, the myrtle oil prolonged pentobarbital-induced sleeping time and there was also half (50%) negative response on the chimney and traction test in a dose-dependent manner.…”
Section: Ethnopharmacological Studiesmentioning
confidence: 99%